Maternal Cadmium Exposure and Neurobehavior in Children: The HOME Study - Yang, Weili (Environ Res, 2020)
BACKGROUND: It is unclear whether cadmium (Cd) exposure during fetal brain development is associated with child neurobehavior. OBJECTIVE: To examine the potential associations between Cd exposure during pregnancy and neurobehavior among children. METHODS: We used data from 276 children in the Health Outcomes and Measures of the Environment (HOME) Study, a well-established prospective pregnancy and birth cohort. We measured maternal urinary Cd concentrations at 26 weeks of gestation. For cognitive function, we assessed Mental Development Index (MDI) and Full-Scale Intelligence Quotient (FSIQ) using the Bayley Scales of Infant Development-II, the Wechsler Preschool and Primary Scales of Intelligence-III, or the Wechsler Intelligence Scales for Children-IV at ages 1, 2, 3, 5, and 8 years. We assessed child behaviors using the Behavior Assessment System for Children-2 at ages 2, 3, 4, 5, and 8 years, yielding four composite measures: Externalizing Problems, Internalizing Problems, Behavioral Symptoms Index, and Adaptive Skills. We used linear mixed models with covariate adjustment to estimate the associations between maternal urinary Cd concentrations and child neurobehavior. RESULTS: We categorized study participants into three groups based on maternal urinary Cd concentrations (Group 1: < limit of detection (LOD), Group 2: 0.06–0.22 μg/g creatinine, Group 3: >0.22 μg/g creatinine). In linear mixed models adjusting for maternal and child characteristics, maternal urinary Cd levels were not significantly associated with cognitive function at ages 1, 2, 3, 5, and 8 years or with behavioral composite measures at 2, 3, 4, 5, and 8 years. CONCLUSIONS: No significant associations were observed between maternal urinary Cd and cognitive or behavioral measures in children at 1 to 8 years of age in this study.